Memelihara Surga Bumi: Analisis Persepsi Gereja terhadap Ekoteologi melalui Sudut Pandang Kejadian 2:15 - Siwy, Hendrico Xanana; Hutagalung, Stimson (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
This research explores the church's perspectives on ecotheology through an examination of Genesis 2:15, which mandates humans to